PRODUCTION PERFORMANCE; DISEASES; SPF-BREEDING; AND RISK ISSUES CONCERNING WHITE SHRIMP, Penaeus vannamei INTRODUCTION INTO INDONESIA - Ketut Sugama; Hessy Novita; Isti Koesharyani (Indonesian Aquaculture Journal, 2006)
In Indonesai, the main .............